A study on gain boosting techniques of cascode amplifier at near-fmax frequencies based on gain plane approach. (June 2021) - He, Fei; Xie, Qian; Wang, Zheng
Abstract: A study on gain boosting techniques of cascode amplifier at near- f max frequencies is presented in this paper. In order to intuitively analyze the effect of the gain boosting technique on the power gain of the amplifier, the gain plane approach is employed. Based on the gain plane approach, the conventional gate inductive gain boosting technique can only improve the unilateral gain ( U ) without improvement on the ratio of the maximum available gain ( G ma ) over U . A revisit on the neutralization technique, which was commonly used for the purpose of stability, is carried out. Our study reveals that the proposed bottom-over-neutralization technique can improve both U and G ma / U, thus leading to higher gain boosting. Based on the proposed technique, an amplifier is implemented in 65 nm CMOS process. The post-layout simulation results exhibit a power gain of 7.74 ​dB in 140 ​GHz, which is 5.2 ​dB higher than the traditional cascode amplifier.